Dimethyl Phthalate Adsorption Using a Composite of Activated Carbon from Black Liquor-diatomite - Yasmine, Luigy Maurizka; Sari, Ajeng Arum; Sulistyaningsih, Triastuti (Universitas Negeri Semarang, 2020)
Dimethyl phthalate is one of the main chemicals in the manufacture of plastics which is harmful to human health because it can be easily absorbed in the body through the skin and is toxic so it is necessary to do a waste treatment process. Adsorption is an alternative method for reducing the levels of dimethyl phthalate in liquid waste. The purpose of this study was to determine the effect of adsorption efficiency on dimethyl phthalate using a composite activated carbon from black liquor-diatomite. A composite activated carbon from black liquor-diatomite were contacted with dimethyl phthalate using the batch method at 120 minutes contact time at 30Ã‚Â°C and pH 5, the variations tested were the concentration and dosage adsorbent. Testing samples using GC-MS. The results showed optimum dimethyl phthalate adsorption at a concentration of 1 ppm with a contact time of 120 minutes, an adsorbent dose of 0.05 gram and a pH of 5 at 64.2%.